Evidence of the magneto-optical Kerr spectral shifts induced by quasi-static strain - Shin, Yooleemi; Lee, Seong-Hyub; Kim, Duck-Ho; Kim, Ji-Wan (American Institute of Physics, 2025)
We demonstrate a dynamical wavelength shift in the magneto-optical Kerr spectrum of a Permalloy thin film, excited by femtosecond laser pulses. Through precise measurements of magneto-optical dynamics with narrow-bandwidth probe pulses, we found systematic variations in the differential Kerr rotation and ellipticity, corresponding to the shape of the static Kerr spectrum. We attribute this behavior to a spectral shift caused by quasi-static strain driven by femtosecond laser-induced heating. Supporting this interpretation, we successfully observed a sign reversal in the static Kerr signal during the demagnetization process. By isolating two contributions to the observed dynamics-a reduction in magnetization due to increased spin temperature and an extra gain from the Kerr spectrum shift-we quantified a horizontal shift of the Kerr spectrum toward shorter wavelengths. (c) 2025 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International (CC BY-NC-ND) license (https://creativecommons.org/licenses/by-nc-nd/4.0/).